Climate change‐associated tree mortality increases without decreasing water availability. (25th August 2015) - Luo, Yong; Chen, Han Y. H.; Enquist, Brian
Abstract Temporal increases of tree mortality have been observed in regions where global warming has decreased long‐term water availability and/or induced droughts. However, temporal decreases in water availability are not a global phenomenon. Understanding how water deficit‐free forests respond to the recent effects of climate change is paramount towards a full appreciation of the impacts of climate change on global forests. Here, we reveal temporally increasing tree mortality across all study species over the last three decades in the central boreal forests of Canada, where long‐term water availability has increased without apparent climate change‐associated drought. In addition, we find that the effects of conspecific tree‐to‐tree competition have intensified temporally as a mechanism for the increased mortality of shade‐intolerant tree species. Our results suggest that the consequences of climate change on tree mortality are more profound than previously thought.